2018
DOI: 10.1021/acschembio.8b00350
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Based Metabolic Labeling for Redirected and Enhanced Immune Response

Abstract: Installation of an antibody-recruiting moiety on the surface of disease-relevant cells can lead to the selective destruction of targets by the immune system. Such an approach can be an alternative strategy to traditional chemotherapeutics in cancer therapy and possibly other diseases. Herein we describe the development of a new strategy to selectively label targets with an antibody-recruiting moiety through its covalent and stable installation, complementing existing methods of employing reversible binding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 75 publications
2
34
0
Order By: Relevance
“…Unsurprisingly, glycoengineering represents an enabling technology for various biomedical applications, namely, both live cell, and extracellular vesicle labeling/tracking, drug‐based cancer theranostics, as well as cell‐based chemo‐ and immunotherapies . Despite an impressive body of literature on these recent advances, tissue engineering concepts exploiting this biomachinery phenomenon are still at their youth.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…Unsurprisingly, glycoengineering represents an enabling technology for various biomedical applications, namely, both live cell, and extracellular vesicle labeling/tracking, drug‐based cancer theranostics, as well as cell‐based chemo‐ and immunotherapies . Despite an impressive body of literature on these recent advances, tissue engineering concepts exploiting this biomachinery phenomenon are still at their youth.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…The azido group can serve as a handle for further labeling for imaging and immune therapy applications. 97 In K562 cells, it took twice as much time for the mono-and disubstituted analogs to complete the cleavage as compared to the unsubstituted one. By combining this monosubstituted disulfide linker system and a MPP, mitochondrial delivery of an HSP90 inhibitor was achieved.…”
Section: Thiol-sensitive Linkersmentioning
confidence: 99%
“…Ac4ManNAz incubation can lead to azidomannose incorporation into cell surface sialic acid. The azido group can serve as a handle for further labeling for imaging and immune therapy applications 97 . In K562 cells, it took twice as much time for the mono‐ and disubstituted analogs to complete the cleavage as compared to the unsubstituted one.…”
Section: Thiol‐sensitive Linkersmentioning
confidence: 99%
“…Redirecting these antibodies to target specic disease cells could lead to adaptive immunities for selective and effective therapy. [31][32][33][34][35][36][37] For instance, a pioneering work from McNaughton's group demonstrated that DNP-modied nanobody 5F7 could recruit anti-DNP antibodies to HER2 + cancer cells and elicit a specic ADCC effect in vitro. However, no in vivo studies have been reported yet.…”
Section: Introductionmentioning
confidence: 99%